The genera Astrenis Förster, 1869 and Phrudus Förster, 1869 (Hymenoptera, Ichneumonidae: Tersilochinae) in the Ukrainian Carpathians - Varga, Oleksandr (Zootaxa, 2023)
The genera Astrenis Förster, 1869 and Phrudus Förster, 1869 from the Ukrainian Carpathians are reviewed. Five species have been found in the studied region, including the first Ukrainian records of Astrenis nigrifacies Viknerg, 2000, and Phrudus badensis Hilpert, 1987. Another Phrudus species, Phrudus carpathicus sp. n., is described and illustrated.